1999
DOI: 10.1080/09640569910975
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation System for National Park Selection in Taiwan

Abstract: The purpose of this study is to analyse the proper factors to be contained in an evaluation system which can then be used to assess areas for designating national parks in Taiwan. In the first phase of work, the Delphi method was used to collect expert opinions on a total of 10 categories of evaluating factors. Six of them are used to assess the characteristics of a site and include diversity, representativeness,naturalness, rarity, fragility and suitability. The other four categories represent the potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The Delphi method is praised as a rapid and relatively efficient means of gathering expert opinion (Kuo and Yu, 1999;Mendoza and Prabhu, 2000), taking much less time and effort for participants in lieu of attending conferences and preparing research papers. It is a useful process for problems where more individuals are needed than can fit in a committee format; when time and cost are prohibitive of further research, meetings or conferences; or when disagreements are so severe that anonymity must be ensured (Linstone and Turoff, 1975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Delphi method is praised as a rapid and relatively efficient means of gathering expert opinion (Kuo and Yu, 1999;Mendoza and Prabhu, 2000), taking much less time and effort for participants in lieu of attending conferences and preparing research papers. It is a useful process for problems where more individuals are needed than can fit in a committee format; when time and cost are prohibitive of further research, meetings or conferences; or when disagreements are so severe that anonymity must be ensured (Linstone and Turoff, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…One long standing criticism of the technique is the lack of a standardized process, and therefore generalizability, due mostly to the variety of problem types to which it has been applied (Linstone and Turoff, 1975;Sackman, 1975). For example, Delphi problem solving has been applied to natural resource issues such as forest biodiversity (Kangas et al, 1998) and sustainability (Mendoza and Prabhu, 2000), heritage tourism (Garrod and Fyall, 2000), environmental disputes (Miller and Cuff, 1986) and forecasting (Ying and Kung, 2000), National Park selection in Taiwan (Kuo and Yu, 1999) and aquatic habitat selection in Lake Ontario (Bush and Lary, 1996). Generalizability, however, is only an issue for applications such as forecasting, and not usually a serious deterrent (Rowe et al, 1991;Ono, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Two experts reviewed the group results after a reminding phone call and stated their agreement with consensus. The similar one-round method is exercised in environmental planning (Kuo & Yu, 1999) and other civil engineering researches (Hartman & Baldwin, 1995).…”
Section: Lowmentioning
confidence: 99%
“…the ecological criteria to assess in ranking environmental sites, and selection of members for expert panels are high among them. With regard to the former criticism, we follow Kuo and Yu (1999) by ensuring that the ecological criteria introduced in our questionnaire were well known in previous research on natural reserves and national parks and the ecological literature 21 . We predicted that this would limit both the need to provide definitions and any potential misunderstanding between the monitoring team and the expert panel.…”
Section: The Delphi Studymentioning
confidence: 99%
“…For example, one reason for such a divergence can be attributed simply to different preference structures between the two groups. In addition, Kuitinen and Törmälä (1994) and Kuo and Yu (1999) have empirically demonstrated that experts and uninformed lay-people focus on different attributes when evaluating the same environmental good. It is therefore likely that the ranking of ecological sites and/or environmental goods would produce a different order from the two sets of respondents.…”
Section: < βmentioning
confidence: 99%